2014
DOI: 10.1080/03079457.2014.956285
|View full text |Cite
|
Sign up to set email alerts
|

Replication characteristics of infectious laryngotracheitis virus in the respiratory and conjunctival mucosa

Abstract: Avian infectious laryngotracheitis virus (ILTV) is an alphaherpesvirus of poultry that is spread worldwide. ILTV enters its host via the respiratory tract and the eyes. Although ILTV has been known for a long time, the replication characteristics of the virus in the respiratory and conjunctival mucosa are still poorly studied. To study these characteristics, two in vitro explant models were developed. Light microscopy and fluorescent terminal deoxynucleotidyl transferase dUTP nick end-labelling staining were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…Consistent with the findings of Reddy et al (17), paracrine-regulated apoptosis of uninfected host cells triggered by ILTV in a host immune response-independent manner was observed in the present study. This interaction between ILTV and uninfected host cells is important for the pathological effects of viral infection and for early viral dissemination.…”
Section: Abstract Alphaherpesviruses Virus-host Interactions Paracrsupporting
confidence: 94%
See 4 more Smart Citations
“…Consistent with the findings of Reddy et al (17), paracrine-regulated apoptosis of uninfected host cells triggered by ILTV in a host immune response-independent manner was observed in the present study. This interaction between ILTV and uninfected host cells is important for the pathological effects of viral infection and for early viral dissemination.…”
Section: Abstract Alphaherpesviruses Virus-host Interactions Paracrsupporting
confidence: 94%
“…These findings are consistent with previous in vitro observations of reduced apoptosis of cells infected with other alphaherpesviruses, such as HSV-1, HSV-2, and suid herpesvirus 1 (18)(19)(20). Interestingly, along with the prosurvival effect of ILTV infection, a recent study by Reddy et al showed that ILTV infection induces apoptosis in bystander cells in vivo (17). However, the biological significance and underlying mechanisms of this phenomenon remain unclear.…”
Section: Abstract Alphaherpesviruses Virus-host Interactions Paracrsupporting
confidence: 91%
See 3 more Smart Citations